An outbreak of acute delirium from exposure to the synthetic cannabinoid AB-CHMINACA. (26th November 2015) - Tyndall, Joseph A.; Gerona, Roy; De Portu, Giuliano; Trecki, Jordan; Elie, Marie-Carmelle; Lucas, Judith; Slish, John; Rand, Kenneth; Bazydlo, Lindsay; Holder, Martina; Ryan, Matthew F.; Myers, Paul; et al.
Abstract : Background : Synthetic cannabinoid containing products are a public health threat as reflected by a number of outbreaks of serious adverse health effects over the past 4 years. The designer drug epidemic is characterized by the rapid turnover of synthetic cannabinoid compounds on the market which creates a challenge in identifying the particular etiology of an outbreak, confirming exposure in cases, and providing current information to law enforcement. Results : Between 28 May 2014 and 8 June 2014, 35 patients were evaluated and treated at the University of Florida Health Medical Center in Gainesville following reported exposure to a synthetic cannabinoid containing product obtained from a common source. Patients demonstrated acute delirium (24) and seizures (14), and five required ventilator support and ICU-level care; none died. The presence of N-[(1S)-1-(aminocarbonyl)-2-methylpropyl]-1-(cyclohexylmethyl)-1H-indazole-3-carboxamide (AB-CHMINACA), or one of its predicted metabolites was confirmed in 15 of 21 cases. A rapid public health response and aggressive public messaging prevented further morbidity, identified the source, and led to law enforcement seizure of the implicated product. Discussion : The significance of this outbreak lies as much in the rapid occurrence of unpredictable, life-threatening adverse health effects from a newly identified synthetic cannabinoid compound as it does in the multidisciplinary investigation and novel partnership between local public health, the laboratory, and the chemical industry, resulting in termination of the outbreak. Conclusion : A coordinated response and collaboration between law enforcement, the local public health, emergency medical services and Health Center staff, were all key interventions in preventing a more substantial public health outbreak resulting from use of a novel synthetic cannabinoid compound. Real time collaborations between toxicology laboratories, suppliers of analytical standards and the public health system may be useful in the face of future novel chemical exposures.